Os nomes da terra Serigy: descrição e análise do glossário etimológico dos nomes da língua tupi na geografia do estado de Sergipe - Matos, Beatriz de Oliveira (2024)
This research analyzes morphosemantic and extralinguistic aspects related to the 341 toponyms present in the Etymological Glossary of the Names of the Tupi Language in the Geography of Sergipe, elaborated by Armindo Guaraná (1916). It considers Toponymy, a discipline that studies place names, as an important element in understanding and preserving the socio-history and linguistic-cultural heritage of a community. The description of this corpus, often dated from a pre-colonial period, refers to the multiethnicity and multilingualism of the territory of Sergipe. The degree of total and/or partial maintenance of this toponymic lexicon in the current geography of the state is considerable, especially in the nomenclature of municipalities, rivers, and beaches. For an extensive study of this important lexicographical source, the theoretical and methodological foundation includes Toponymy, Lexicography, the History of Brazilian Portuguese, Geography, and the History of Sergipe. This approach aims to catalog and classify these place names. The classification of the toponymic corpus confirms the intersection of language, culture, and environment in these semantically opaque signs, whose physical-natural characteristics involve local hydrography, topography, flora, and fauna, as evidenced by literature (Dick, 1990, 1992; Santos, 2012; 2019; among others).